Comparison of Transjugular Intrahepatic Portosystemic Shunt in the Treatment of Cirrhosis With or Without Portal Vein Thrombosis: A Retrospective Study - Wang, Hong-Liang; Lu, Wei-Jie; Zhang, Yue-Lin; Nie, Chun-Hui; Zhou, Tan-Yang; Zhou, Guan-Hui; Zhu, Tong-Yin; Wang, Bao-Quan; Chen, Sheng-Qun; Yu, Zi-Niu; Jing, Li; Sun, Jun-Hui (Frontiers in Medicine, 2021)
Aim: The purpose of our study was to conduct a retrospective analysis to compare the effectiveness of transjugular intrahepatic portosystemic shunts (TIPSs) in the treatment of patients with cirrhosis with or without portal vein thrombosis (PVT). Methods We included a total of 224 cirrhosis patients successfully treated with TIPS between January 2015 and January 2018, including 78 cirrhosis patients with PVT (34.8%) and 146 without PVT (65.2%). Our subjects were followed at least 1 year after treatment with TIPS. Data were collected to estimate the mortality, shunt dysfunction and complication rates after TIPS creation. Results During the mean follow-up time of 19.46±12.83 months, 32 (14.3%) patients died, 18 (8.0%) developed shunt dysfunction, and 48 (21.4%) experienced overt hepatic encephalopathy (OHE). No significant differences in mortality (P=0.208), shunt dysfunction (P= 0.159) or OHE (P= 0.558) were noted between the groups. Age, Model for End-Stage Liver Disease (MELD) score and refractory ascites requiring TIPS were risk factors for mortality. A history of diabetes, PTVE, 8-mm diameter stent and PLT increased the risk of shunt dysfunction. The prevalence of recurrent ascites and variceal bleeding was comparable between the two groups (16.7% vs. 15.8% P=0.859 and 2.6% vs. 3.4% P=0.724, respectively). Conclusion TIPS is feasible in the management of cirrhosis with PVT. No significant differences in survival or shunt dysfunction were noted between the PVT and No-PVT groups. The risk of recurrent variceal bleeding, recurrent ascites and OHE in the PVT group was generally similar to that in the No-PVT group. TIPS represents a potential feasible treatment option in cirrhosis patients with PVT.